Can Transient Drop in Blood Pressure in High-Risk Hypertensive Patients Cause Small Cerebral Infarcts?. (14th February 2013) - Bhagavati, Satyakam; Choi, Jai
Abstract : Background . Multiple, simultaneous, acute cerebral infarcts in different arterial territories are usually secondary to embolic occlusion of multiple cerebral arteries. We observed, however, that no cardiac or aortic source could be found in many of these patients. We therefore undertook this study to attempt to identify other factors that may be important in the causation of these infarcts. Materials and Methods . We performed a five-year retrospective review of all patients with multiple, near simultaneous, acute cerebral infarcts detected on diffusion-weighted MRI scans. Results . We identified 78 patients with acute infarcts, in different cerebral arterial territories. We found a cardiac embolic source in 15 (19 percent) patients. Forty-one patients (53%) had no obvious cause for their infarcts after detailed cardiovascular and hematological evaluation. In 16 of these patients (20% of all 78 patients), all with a history of chronic hypertension who had multiple, acute, small (<2 cms), deep subcortical or superficial cortical infarcts (and most, 93%, with extensive evidence of chronic small vessel disease on MRI FLAIR images), blood pressure was low or normal on initial presentation (mean arterial pressure, MAP: 85 ± 11.4 mm Hg). Analysis of the last prestroke blood pressure, within the previous 1 to 11 days available in 13 of 16 patients, revealed much higher BP (MAP: 113.6 ± 11.3 mm Hg), indicating a mean drop of 25.1 percent (range 11 to 44 percent). Two weeks after the stroke, blood pressure had risen again to greater than 160/100 mm Hg (MAP: 128.2 ± 14.3). Conclusion . Our study suggests that transient drop in blood pressure in high-risk hypertensive patients with severe, small vessel disease may sometimes result in small, cerebral infarcts. More research is needed to further clarify and confirm this possibility.